Predictors of frailty syndrome among community-dwelling elderly in Kuala Nerus, Terengganu - Ab. Aziz, Nur Hafizah (2017)
Poor health outcomes including frailty syndrome is common among the elderly as they aged. Characterized by decreasing physiological reserves, frailty syndrome is associated with increased risk of disability, morbidity and mortality. The aims of this study were to determine the prevalence of frailty syndrome and their associations with socio-demographic and socioeconomic status, psychosocial factors, functional factors and anthropometric indicators among community-dwelling elderly in Kuala Nerus. A cross-sectional study of 279 elderly respondents, with 90% of response-rate; consisted of 118 (42.3%) male and 161 (57.7%) female were randomly selected and interviewed. Data collection was conducted by using a set of questionnaire containing information about socio-demographic and socioeconomic status, psychosocial factors, functional assessments, anthropometric measurements and frailty syndrome assessments. Psychosocial factors was assessed by questionnaires adapted from validated SF-36 and questionnaires on social relationship and participation. Cognitive status was assessed by Elderly Cognitive Assessment Questionnaire (ECAQ). Functional status was assessed by Activity Daily Living (ADL) Instrumental Activity of Daily Living (IADL) and Elderly Mobility Scale (EMS) questionnaires. The anthropometric indicators measured were Body Mass Index (BMI), body parts circumferences, total body fat and Skeletal Muscle Index (SMI). Frailty syndrome was characterized by using validated Fried’s (2001) phenotype. Majority (60.2%) of the respondents were classified as young-old elderly (60-74 years old), with mean age 73.3 ± 6.1 years old. Most respondents were living with others (82.4%), have no spouse (51.3%), had formal education (58.8%), unemployed (83.5%), had low income, which was below RM500 (43.7%), lived in a small household size (66.3%) and depended on others for financial dependency (78.5%). Majority of respondents participated frequently in leisure activities (79.6%), feast (66.3%) and religious activities; prayed together in mosque (57.7%), tahlil recitation (55.6%) and religious talk (58.1%). There was 88.2% respondents with no depression. About 18.6% of respondents had cognitive impairment, dependent in mobility (5.0%), had difficulties to perform ADL (87.5%) and IADL (70.6%). Majority of the respondents (48.7%) have normal BMI and have low risk of muscle wasting. The prevalence of frailty syndrome was 18.3%. In bivariate analysis, the factors associated with frailty syndrome were advanced age, unmarried, illiteracy, unemployed, lack of social relationship with siblings and relatives, lower participation in leisure activities, feast, gotong-royong and religious activities, cognitive impairment, mobility dependent, difficulties in performing ADL and IADL tasks, lower body mass index, middle-upper arm circumference, calf circumference, body fat and lean body mass. In multivariate analysis by binary logistic regression, unmarried [odds ratio (OR): 3.87; 95% confidence interval (CI): 1.008 - 14.878], lower scores of Physical Component Scale (PCS) [OR: 0.93; 95% CI: 0.886 – 0.967], difficulties in performing ADL tasks [OR: 0.18; CI: 0.044 – 0.773] and lower body mass index [OR: 0.697; 95% CI: 0.530 – 0.916] were significantly associated with frailty syndrome. The characteristics and predictors of frailty syndrome among elderly population gave an overview that can be used as the baseline data on frailty syndrome for the intervention program to minimize the worse effects of frailty syndrome.